Propuesta de un diseño de sistema contable para emprendedores: caso Estudio Heladería Antojitos (2022)
In the present research work it was proposed to desi gn an accounting information system that provides an entrepreneur with the necessary tools to control the information that his business generates; it is important to distinguish that in the ventures, even if their ideas are innovative, one of their biggest declines is in the financial management that they impart to the finances of the business, causing their permanence in the market to be shortened by the decisions they have made and that has led them to the closure of their companies